From rejection to publication: A content analysis of reviewers’ feedback to strengthen research papers in English education - Yustinus Calvin Gai Mali (Journal on English as a Foreign Language, 2026)
Academics need to publish research papers in scholarly journals successfully for various purposes. However, practical tips and tricks to help readers successfully publish their research in academic peer-reviewed journals, particularly in English education and teaching-related fields, remain limited. As a response, this study aims to present lessons learned from various journal reviewers on ways to substantially enhance a research paper so that it can be successfully published in a reputable academic journal, particularly in the English education and teaching-related fields. To meet the research objective and address the empirical gap in the literature, a qualitative content analysis was conducted on reviewers’ feedback from nine manuscript submissions (both accepted and declined) to SCOPUS (Q1 and Q2) and SINTA 2-indexed journals. The analysis results showed various lessons learned summarized in a checklist table, providing specific, actionable writing guidelines for each section of a paper, emphasizing clarity, coherence, detail, and argumentation. Main research implications regarding the importance of reviewers’ feedback for substantially enhancing a research paper and the essence of using the text deconstruction strategy in writing a quality, publishable research paper are discussed.